Reduced caregiving quality measured during the strange situation procedure increases child's autonomic nervous system stress response - Franziska Köhler-Dauner; Eva Roder; Sabrina Krause; Anna Buchheim; Harald Gündel; Jörg M. Fegert; Ute Ziegenhain; Christiane Waller (BMC, 2019)
Abstract Background Dysfunctional maternal behavior has been shown to lead to disturbances in infant's regulatory capacities and alterations in vagal reactivity. We aim to investigate the autonomic nervous system (ANS) response of the child during the strange situation procedure (SSP) in relation to the quality of maternal behavior. Methods Twelve month after birth, 163 mother-child-dyads were investigated during the SSP. Heart rate (HR) and both, the parasympathetic branch (PNS) via the respiratory sinus arrhythmia (RSA) and the sympathetic branch (SNS) via the left ventricular ejection time (LVET) of the ANS were continuously determined during the SSP using electrocardiogram (ECG) and impedance cardiogram (ICG) measures. Maternal behavior was assessed by using the AMBIANCE measure. Results The ANS response in infants of mothers with disruptive behavior compared to infants of non-disruptive mothers was significantly altered during the SSP: HR increased especially when infants of disruptive mothers were alone with the stranger (F (1, 161) = 4.15, p = .04) with a significant vagal withdrawal when being in contact with the stranger despite of presence of the mother (F (1, 161) = 5.11, p = .03) and a significant increase in vagal tone during final reunion (F (1, 161) = 3.76, p = .05). HR increase was mainly based on a decrease in LVET (F (1, 161) = 4.08, p = .05) with a maximum infant's HR when the stranger came into the room instead of the mother. Conclusion Both, SNS and PNS branches of the child are significantly altered in terms of an ANS imbalance, especially during contract to a stranger, in relation to dysfunctional maternal behavior. Our findings suggest the importance of supporting high quality caregiving that enables the infant to adapt adequately to stressful interpersonal situations which is likely to promote later health.